Immunohistochemical expression of cathepsin L in atopic dermatitis and lichen planus - Zeinab A El Ashmawy; Amal A El-Ashmawy; Naeim M Abd El-Naby; Hussein M Ghoraba (Wolters Kluwer Medknow Publications, 2015)
Background: Cathepsin L is a member of papain superfamily. It seems to promote T-cell survival, selection maturation in the thymus and enhance the antigen presentation. Cathepsin L plays an important role in tumor necrosis factors (TNF-α) induced cell death. Also it degrades the tight junction between cornedesomses in the epidermis. Elevated expression of cathepsin L has been found in many inflammatory and neoplastic diseases. Objective: The aim of this study was to determine immunohistochemical expression of cathepsin L in atopic dermatitis (AD) and lichen planus (LP) patients in order to evaluate its role in the pathogenesis of both diseases. Materials and Methods: This study included 15 patients with AD (Group I), 15 patients with LP (Group II), in addition to 10 healthy skin specimens served as controls (Group III). Punch biopsies were taken from lesional skin of the patients and controls for immunohistochemical detection of cathepsin L expression. Results: Highly significant increase was found in cathepsin L expression in AD and LP patients compared to controls [P = 0.001]. Conclusion: Cathepsin L could be implicated as an important protease in the pathogenesis of AD and LP. It could be a useful marker for assessing AD severity.